2022
DOI: 10.2147/ott.s377638
|View full text |Cite
|
Sign up to set email alerts
|

Chronological Liquid Biopsy Reveals the Impact of Platinum-Based Chemotherapy on a Prostate Cancer Patient’s CDK12 Mutation: A Case Report

Abstract: CDK12 (Cyclin-Dependent Kinase 12)-mutated prostate cancer patients often respond badly to current therapies. Immunotherapy and platinum-based chemotherapy are recommended based on the molecular features of CDK12 -mutated tumors, but the reported patient outcomes are still unsatisfying. Here we report a prostate cancer patient with CDK12 somatic mutation who received multiple therapy options, including platinum-based chemotherapy and immunotherapy. His s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“… Zhu et al (2022) reported a case of a 55-year-old male with CDK12-mutated PCa diagnosed with the help of circulating tumor DNA. Basnet et al (2017) present a unique case of a male patient aged 65 years with mCRPC, and primarily local failure in the pelvis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Zhu et al (2022) reported a case of a 55-year-old male with CDK12-mutated PCa diagnosed with the help of circulating tumor DNA. Basnet et al (2017) present a unique case of a male patient aged 65 years with mCRPC, and primarily local failure in the pelvis.…”
Section: Resultsmentioning
confidence: 99%
“… Zhu et al (2022) primarily administered Cis-Platinum chemotherapy to the CDK12 mutated PCa patient. Essentially, a literature-supported PD-1 inhibitor was administered in the last year of survival ( Zhu et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite good initial response to Androgen Deprivation Therapy (ADT), tumors eventually progress to metastatic castration resistant PCa (mCRPC). Liquid biopsy assays, analyzing circulating free tumor DNA (ctDNA) or circulating tumor cells (CTCs) in plasma or other body fluids have proven as a useful source for biomarkers and have already entered the clinics [1] as to this date, mCRPC remains an incurable disease [1] CDK12(Cyclin-Dependent Kinase)-mutated prostate cancer patients are likely to benefit from platinum-based chemotherapy, especially with the help of dynamic ctDNA-based liquid biopsies to monitor their CDK12 mutation status [2]. Liquid biopsy is a powerful tool for isolating genetic material, proteins, and whole tumor cells from the blood.…”
mentioning
confidence: 99%